ANTHROPOLOGIZATION OF SCIENCE: FROM THE SUBJECT OF COGNITION TO THE RESEARCHER’S PERSONALITY - N. V. Kryvtsova; I. A. Donnikova (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
Purpose. With the consideration of anthropological tendencies in modern science, the purpose of the article is to analyze the problem of the subject of cognition, philosophical-psychological rationale for the need to complement it by the concept of "the researcher’s personality". Theoretical basis. The authors rely on post-non-classical methodological tools and basic principles of complexity theory (autopoiesis, auto-eco-organization, synergy, syzygy, targeted and cyclic determination), as well as theoretical provisions of epistemological constructivism (enactivism), the results of theoretical and empirical psychological studies. In them, authors revealed psychological features of the potential of self-realization of a person prone to innovation and research activities and transfessionalism, including the resources and reserves of the researcher’s personality. Originality. The concept of the subject of (scientific) cognition is expanded by the concept of "researcher’s personality" and derivative concepts that describe the dynamics of self-harmonization of originative co-generative strengths and opportunities of self-realization of an enlightened person, reveal the degree of correlation in the cognition of the subjective and objective dimensions of his life. It is substantiated that further analysis of the problem of anthropologization of science requires appropriate onto-epistemological grounds that reveals the unity of cognition-education-skill as an essential characteristic of the maturity of the researcher’s personality of scientific knowledge. Conclusions. In the context of anthropological shifts in modern science, the philosophical-psychological analysis of the problem of the subject of cognition is actualized. The psychological research proves the advisability of using the "researcher’s personality" concept as a basic one for understanding the formation of an enlightened human-creator, capable of auto-eco-organization, self-transcendence, and syzygy with the Universe at different levels of innovational research activity. The self-realization of the researcher-personality is a way-search for the authenticity of the multiform unity of life, the personal meaning of scientific truth, and the self-harmonization of the originative co-generative co-determinative strengths in the knowledge of an enlightened person. Including the concept of the subject of cognition in the ontology of the unity of difference-multidimensional poly-essential autopoetic integrity, the anthropologization of science is intended to revive the ancient idea in the unity of truth ("ἀλήθεια"), education ("παιδεία") and skill ("τέχνη") of a scientist, defining the ideal of a modern human-transfessional.